Binaries discovered by the MUCHFUSS project: SDSS J08205+0008 - An eclipsing subdwarf B binary with a brown dwarf companion - Geier, Stephan; Schaffenroth, Veronika; Drechsel, Horst; Heber, Ulrich; Kupfer, Thomas; Tillich, A.; Ostensen, R. H.; Smolders, K.; Degroote, P.; Maxted, P. F. L.; Barlow, B. N.; Gaensicke, B. T.; et al. (Astrophysical Journal Letters, 2011)
Hot subdwarf B stars (sdBs) are extreme horizontal branch stars believed to originate from close binary evolution. Indeed about half of the known sdB stars are found in close binaries with periods ranging from a few hours to a few days. The enormous mass loss required to remove the hydrogen envelope of the red-giant progenitor almost entirely can be explained by common envelope ejection. A rare subclass of these binaries are the eclipsing HW Vir binaries where the sdB is orbited by a dwarf M star. Here, we report the discovery of an HW Vir system in the course of the MUCHFUSS project. A most likely substellar object (≃0.068 M⊙) was found to orbit the hot subdwarf J08205+0008 with a period of 0.096 days. Since the eclipses are total, the system parameters are very well constrained. J08205+0008 has the lowest unambiguously measured companion mass yet found in a subdwarf B binary. This implies that the most likely substellar companion has not only survived the engulfment by the red-giant envelope, but also triggered its ejection and enabled the sdB star to form. The system provides evidence that brown dwarfs may indeed be able to significantly affect late stellar evolution. © 2011. The American Astronomical Society. All rights reserved.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: spectroscopic; brown dwarfs; stars: horizontal-branch; stars: individual